VIOLENCIAS EN LA ESCUELA: PROTAGONISMO, GÉNERO Y DESIGUALDAD - Villanueva, Concepción Fernández; Adam, Joyce Mary [UNESP] (Centro de Estudos Educação e Sociedade, 2020)
This article analyses gender differences in school violence from an interactionist perspective. It presents a qualitative analysis of violent incidents occurred in two schools in the outskirts of São Paulo (Brazil), collected through group interviews with male and female young scholars. Despite the fact that the investigation has located protagonisms of the female students violence, women in general are less protagonists and more victims than men and those differences are accentuated in the violence directed against the school institution. Explanatory arguments are similar although men emphasize rivalry against school institution and women interpersonal rivalry

El trabajo aborda las diferencias de género en violencia en la escuela desde una perspectiva interaccionista. Se realiza un análisis de incidentes de violencia ocurridos en dos escuelas de la periferia de São Paulo (Brasil) relatados en entrevistas de grupo a jóvenes escolares de ambos sexos. A pesar de que la investigación haber localizado protagonismos de violencia de alumnas, las mujeres son menos protagonistas y más víctimas que los varones y las diferencias se acentúan en la violencia dirigida contra la institución escolar. Los argumentos explicativos son similares aunque los varones resaltan la rivalidad contra la escuela y las mujeres la rivalidad interpersonal.
VIOLENCE IN SCHOOL: PROTAGONISM, GENDER, AND INEQUALITY
Keywords: School; Violence; Gender; Inequalities